Addressing inequities and meeting needs of Indigenous communities in floodplain management - Zimmerman, Olivia; Eison, Tanya; Carey, Robert; Levin, Phillip S. (Frontiers in Climate, 2024)
Anthropogenic impacts have altered and degraded global ecosystems. Integrated resource management offers an important solution to enhance collaboration, holistic thinking, and equity by considering diverse perspectives in decision making. In Washington State, Floodplains by Design (FbD) is a floodplain management and habitat restoration program that emphasizes bringing together diverse stakeholders and supporting conversations between local, state, and Tribal governments while enhancing environmental justice in the region. Marginalized communities continue to be disproportionately impacted by environmental disturbances. Our project interviewed Tribal natural resource managers to assess the degree to which they felt FbD was supporting their community's needs. Our research asked three questions: 1) What Tribal needs and inequities associated with floodplains are identified by Tribal natural resource managers? 2) Are these needs and inequities being addressed by FbD? and 3) How can FbD better address these needs and inequities moving forward? We found that while the integrated approach of FbD was driving solutions in some realms, there are ways in which the program could better support needs and address inequities in Tribal communities. Specifically, we found that conventional responses to environmental challenges are rooted in modernist paradigms that have created persistent dualities, including that of human-nature and human-nonhuman. Such a paradigm is in conflict with wellbeing and self-determination of Tribal cultures that are deeply connected to Pacific salmon. In closing, we provide insights on these mechanisms and offer solutions moving forward.